EXPLORING THE DRIVERS OF CUSTOMER LOYALTY FROM AN ISLAMIC PERSPECTIVE: A CASE STUDY OF BANK ACEH SYARIAH - Yusniar, Yusniar (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study explores customer loyalty at Bank Syariah Indonesia in Aceh, focusing on the role of Sharia implementation in shaping customer behavior. Using a quantitative research design, data were gathered through interviews, observations, and questionnaires distributed via a non-probability sampling method. The aim is to identify the factors that drive customer loyalty at Bank Syariah Indonesia in Banda Aceh. The results demonstrate that brand image plays a crucial role in influencing customer loyalty. Consequently, bank leadership should emphasize enhancing brand image as part of their strategy to retain loyal customers. Loyalty is reflected in customers’ positive attitudes, such as sharing favorable experiences and recommending the bank to others, while negative attitudes include spreading unfavorable opinions and switching to competitors. From an Islamic viewpoint, customer loyalty goes beyond mere transactional commitment; it is grounded in Islamic principles and values. True loyalty involves not only knowledge and practice of worship but also sincere faith in Allah SWT, which collectively shapes a customer’s ethical and spiritual dedication to the institution.